AN OVERVIEW OF INDONESIAN LOGISTIC PERFORMANCE AND THE SISLOGNAS 2012 - IRWAN CHAIRUDDIN (Institut Transportasi dan Logistik Trisakti, 2015)
Indonesian Logistic Performance Ranking is lower than other ASEAN Countries so it needs a lot of concerns, because the economy is strongly influenced by the condition and system of the logistics. The purpose of this article is to find out Indonesian Logistics Performance by analyzing the World Bank indicators and description, compare it to the opinion of the practitioners in the logistics sector. Indonesian government is facing this logistic problem as a system to increase the national competitiveness and suport the implementation of the Accelaration of Indonesian Economy Development Masterplan 2011-2025. By applying the “Wilcoxon Sign Test”, proofing that there are no significant differences between the World Bank and the logistic practitioners in scoring the logistics indicators.